2016
DOI: 10.5937/tehnika1601016m
|View full text |Cite
|
Sign up to set email alerts
|

Swelling kinetics and impregnation of PLA with thymol under supercritical CO2 conditions

Abstract: The present work was aimed to study swelling kinetics of polylactic acid (PLA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, the samples that were treated with scCO 2 at just 100 bar while the temperature was increased from 35 until 55 °C demonstrated a lesser swelling effect. In accordance, Milovanovic et al [ 5 ] studied the swelling pattern of PLA cylinders, which had been previously produced from melted PLA beads, under scCO 2 at 100 bar, and they observed that temperature increments (40–75 °C) diminished the swelling effect.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the samples that were treated with scCO 2 at just 100 bar while the temperature was increased from 35 until 55 °C demonstrated a lesser swelling effect. In accordance, Milovanovic et al [ 5 ] studied the swelling pattern of PLA cylinders, which had been previously produced from melted PLA beads, under scCO 2 at 100 bar, and they observed that temperature increments (40–75 °C) diminished the swelling effect.…”
Section: Discussionmentioning
confidence: 60%
“…Polyesters, and specially polylactic acid (PLA) in its poly-l-lactide (PLLA) and poly-d,l-lactide (PDLLA) forms, are the most widely studied polymers for the development of bioresorbable drug-delivering implantable devices. Some examples can be found in the literature regarding the supercritical impregnation of drugs or bioactive substances into lactic acid polymers shaped as films, thin discs [ 4 , 5 , 6 ], microparticles [ 7 ], or porous structures [ 8 , 9 , 10 , 11 ]. However, no references have been found to use supercritical impregnation on PLA filaments, despite some studies having been conducted on this type of impregnation into surgical suture materials [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when T is around the working conditions, the polymer can be still in the glassy state [ 39 ], although some volume variations can occur. To evaluate these mechanical changes, the percentage of volume increment or swelling of the filament according to the equation given below [ 40 ], where is the swelling percentage, V is filament volume after the impregnation, and is the original filament volume before being impregnated: …”
Section: Methodsmentioning
confidence: 99%
“…PDLLA swells in scCO 2 and forms a homogeneous polymer column at the bottom of the tube. Further, we can assume that the diffusion of the CO 2 in PDLLA and the swelling of PDLLA are orders of magnitude faster than TEMPONE diffusion in swollen PDLLA [ 86 , 87 , 88 ], and we can suppose the areas achieved by the probe to be completely swollen. The diffusion of TEMPONE in PDLLA hence could be described as non-stationary one-component diffusion into a plane sheet from a medium with constant solute concentration.…”
Section: Methodsmentioning
confidence: 99%